(untitled) (Vietnam Journal of Community Medicine, 2025)
Objectives: Evaluation of breastfeeding knowledge of postpartum mothers at Dien Bien Provincial General Hospital. Methods: Cross-sectional descriptive study with convenience sampling method, self-administered questionnaire to describe the knowledge status of pregnant women. Results: 81.7% of mothers know that the best food for children under 6 months old is breast milk. Most mothers (91.7%) believe that the benefits of breast milk are adequate nutrition and 81.7% of mothers believe that breast milk helps children fight diseases. 16.7% of mothers have the correct knowledge that they should breastfeed their children as soon as possible after birth. 86.7% of mothers know about colostrum and believe that it should not be discarded. 56.7% of mothers know that they need to hold and burp their children after feeding. Only 5% of mothers know the correct way for babies to latch on to the breast and 36.7% of mothers have the correct knowledge about when to wean their babies. Conclusion: Breastfeeding knowledge of postpartum mothers is relatively good with 73.3% having satisfactory knowledge and 26.7% having inadequate knowledge. Factors related to breastfeeding knowledge include: place of residence, age, occupation, number of children.